Can seasonal differences influence food web structure on preserved habitats? Responses from two Brazilian streams - Ceneviva-Bastos, M. [UNESP]; Casatti, L. [UNESP]; Uieda, V. S. [UNESP] (Springer Nature, 2012)
Many studies on Neotropical streams have reported seasonal changes in the diet offish, although studies that evaluate the influence of these temporal differences on the entire web are very scarce. Under the hypothesis that trophic interactions and the food web structure are under seasonal influences, two forested streams (named S1 and S2) were sampled during the wet and dry periods. The samplings were conducted in August 2007 and April 2008 and included algae, macrophytes, plankton, macroinvertebrates, and fish. All heterotrophic taxa sampled were submitted to diet analysis. The similarity among samples was estimated by a cluster analysis using quantitative data of environmental variables, community attributes, and food web properties. A total of 2,250 individuals of 139 trophic species were identified. The food webs were mainly detritus-based, which resulted in a great proportion of trophic species at the first trophic level and high omnivory in all samples. All fish species were top species because they had no predators. The SI stream, predominantly composed of a sandy substrate, presented lower abundance than the predominantly rocky S2 stream in both dry and wet periods, although richness was similar. Cluster analysis demonstrated that environmental attributes were more similar between seasons, community attributes were more similar between streams, and food web parameters were very similar (94% similarity) both between streams and seasons. Therefore, we concluded that although environmental attributes varied temporally and community attributes varied spatially, the trophic relationships and overall food web structure of these preserved streams remain similar. © Akadémiai Kiadó, Budapest.
Keywords: Detritus; Feeding; Forest fragments; Omnivory; Trophic interactions